2009
DOI: 10.1158/0008-5472.can-08-4156
|View full text |Cite
|
Sign up to set email alerts
|

B-MYB Is Required for Recovery from the DNA Damage–Induced G2 Checkpoint in p53 Mutant Cells

Abstract: In response to DNA damage, several signaling pathways that arrest the cell cycle in G(1) and G(2) are activated. The down-regulation of mitotic genes contributes to the stable maintenance of the G(2) arrest. The human LINC or DREAM complex, together with the B-MYB transcription factor, plays an essential role in the expression of G(2)-M genes. Here, we show that DNA damage results in the p53-dependent binding of p130 and E2F4 to LINC and the dissociation of B-MYB from LINC. We find that B-MYB fails to dissocia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 42 publications
5
91
0
1
Order By: Relevance
“…This activity of B-Myb is thought to explain how it promotes recovery from the DNA damage-induced G2 checkpoint 12 . To investigate whether cyclin F and B-Myb are functionally linked in regulating the G2/M checkpoint, we codepleted B-Myb and cyclin F and treated the cells with IR to induce DNA damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity of B-Myb is thought to explain how it promotes recovery from the DNA damage-induced G2 checkpoint 12 . To investigate whether cyclin F and B-Myb are functionally linked in regulating the G2/M checkpoint, we codepleted B-Myb and cyclin F and treated the cells with IR to induce DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, binding of B-Myb was observed in promoters of many genes controlling the transition from G2 to M phase, and contact to promoter regions appeared to depend on the CHR element, but not on Myb-binding sites 11 . Consistently, B-Myb is thought to be required for the cell cycle recovery from the DNA damageinduced G2 checkpoint 12 .…”
mentioning
confidence: 89%
“…Similarly, small interfering RNA (siRNA)-mediated depletion of FoxM1 is detrimental to G2 recovery and can only be rescued by inducible siRNA-resistant FoxM1 when it is present throughout the arrest (Alvarez-Fernández et al, 2010). In conjunction with FoxM1, BMyb contributes to the expression of G2-specific genes during an arrest in G2 and is required for checkpoint recovery in p53-deficient cells (Mannefeld et al, 2009). Damaged G2 cells must thus carefully suppress the Cdk-driven G2 transcriptional programme during the arrest to prevent premature mitotic entry, but at the same time retain sufficient expression to maintain (A) During normal G2 progression, the expression of G2-specific genes increases to allow timely mitotic entry.…”
Section: G2 Checkpoint Recovery -Maintaining Reversibility Balancing mentioning
confidence: 99%
“…p53 counteracts the transcription of many G2-specific genes to contribute to the maintenance of a G2 arrest, and upregulation of p53 is sufficient to permanently arrest cells in G2, even in the absence of DNA damage (Agarwal et al, 1995;Bunz et al, 1998;Krenning et al, 2014;Mannefeld et al, 2009;Riley et al, 2008). Consequently, cells must also balance p53 activity to maintain the reversibility of a G2 arrest (Fig.…”
Section: G2 Checkpoint Recovery -Maintaining Reversibility Balancing mentioning
confidence: 99%
“…In fact, a recent report has showed that B-Myb, similar to FoxM1, is also required for recovery from a DNA damage-induced G 2 arrest. 17 In addition to transcription of G 2 -specific genes, Cdk activity may also regulate protein degradation during a checkpoint-dependent arrest. In an unperturbed G 2 phase, the ubiquitin ligase APC/C-Cdh1 remains inactive due to Cdk-dependent phosphorylation of Cdh1.…”
Section: Transcriptional Repression and Recovery Competencementioning
confidence: 99%